High-quality electrical transport using scalable CVD graphene. (17th August 2020) - Pezzini, Sergio; Mišeikis, Vaidotas; Pace, Simona; Rossella, Francesco; Watanabe, Kenji; Taniguchi, Takashi; Coletti, Camilla
Abstract: Producing and manipulating graphene on fab-compatible scale, while maintaining its remarkable carrier mobility, is key to finalize its technological application. We show that a large-scale approach (chemical vapor deposition on Cu followed by polymer-mediated semi-dry transfer) yields single-layer graphene crystals fully comparable, in terms of electronic transport, to micro-mechanically exfoliated flakes. Hexagonal boron nitride is used to encapsulate the graphene crystals—without taking part to their detachment from the growth catalyst—and study their intrinsic properties in field-effect devices. At room temperature, the electron-phonon coupling sets the mobility to ∼ 1.3 × 10 5 cm 2 V −1 s −1 at ∼ 10 11 cm −2 concentration. At T = 4.2 K, the mobility (>6 × 10 5 cm 2 V −1 s −1 at ∼ 10 11 cm −2 ) is limited by the devices' physical edges, and charge fluctuations < 7 × 10 9 cm −2 are detected. Under perpendicular magnetic fields, we observe early onset of Landau quantization ( B ∼ 50 mT) and signatures of electronic correlation, including the fractional quantum Hall effect.